Linguistic Intelligence for Cross-Cultural Adaptation of Indonesian Beginner Students in Egypt - Wahyuni, Imelda; Rachmat, Muh Zacky Fadhil (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
While previous research has extensively examined cross-cultural adaptation among international students, limited attention has been given to the specific role of linguistic intelligence in facilitating this process, particularly among Indonesian beginner students in Arab-speaking contexts. This study investigates how linguistic intelligence influences cross-cultural adaptation of Indonesian students in Egypt. Employing a mixed-method approach, this research combines field data from 120 Indonesian students' lived experiences in Egypt with a systematic literature review of relevant studies. Quantitative analysis reveals a significant positive correlation (r=0.72, p<0.01) between linguistic intelligence dimensions and adaptation outcomes, while qualitative findings highlight language learning strategies, communicative confidence, and sociolinguistic awareness as critical adaptation mechanisms. Results demonstrate that students with higher linguistic intelligence exhibit superior cultural adjustment, academic performance, and social integration. The study's implications suggest that pre-departure orientation programs should incorporate linguistic intelligence development alongside traditional language training, and educational institutions should assess students' linguistic competencies to provide tailored support systems for enhanced cross-cultural adaptation success.